Labor heterogeneity and total factor productivity: evidence from Vietnamese manufacturing private sector - Huu Trinh Nguyen; Dai Le; Dung Dang; Tuan Nguyen (Management Science Letters, 2020)
This paper investigates firm heterogeneity in total factor productivity across Vietnam domestic private sector with sixteen manufacturing subindustries over the period 2010-2016, with a focus on labor size and based on total factor productivity (TFP); including TFP level, TFP distance, and TFP dispersion. Our results indicate that, in the private sector, labor heterogeneity on productivity are very dependent on specific manufacturing sectors, and on type of TFP. From an industrial policy perspective, there is hence productivity related reason on why Vietnamese policy makers should prefer large and extremely large firms over small and medium enterprises (SMEs) in some manufacturing and vice versa. Our results provide a support for both SMEs and large private consortiums, depending on specific manufacturing sectors. In addition, since there is a strong evidence to suggest that labor heterogeneity in TFP exists in some manufacturing sectors, the rationality behind policies to support SMEs and large firms at every manufacturing sectors seems to be questionable.